VOLUNTARY TAX COMPLIANCE WAJIB PAJAK PERUSAHAAN PERHOTELAN: DETERMINAN, KEPERCAYAAN DAN KEKUASAAN LEGITIMASI - Hakim, Zulkarnain; Handajani, Lilik; Inapty, Biana Adha (Jurnal Akuntansi, 2017)
The aim of this research are to give empirical proof about: (1)the influence procedural juctice and moral obligation toward voluntary tax compliance. (2) the influence of trust within mediation influence between procedural juctice and moral obligation toward voluntary tax compliance. (3) the influence of legitimation power within moderation influence of tust toward voluntary tax compliance. Data collection in this research using quisioner. As many as 108 quisioner divided to manager and accountan in each hotel. From data above, 91 quisioner are given back by responden. So, 91 quisioners can be used in analysis proses. The result of this research eviden, the procedural jucticeand moral obligation ralated to voluntary tax compliance. The result of this research also eviden the role mediation of trust. Voluntary tax compliance occurs becouse of procedural juctice and moral obligation direct to voluntary tax compliance through mediation of trust, and realionship between trust and voluntary tax compliance are not moderation by legitimation power.